Brash ensemble (Raton Range Raton, NM)
Article is about six Ratonians getting together for the lighting of the Christmas Tree Downtown to play Christmas music.
Newspaper Article + Photograph of Randy Rubin, Julian Warner, Mark Morries, David Manfredi, Jim White and Pat Chavez.
Master list item #: 32
File location is in the Raton file Cabinet
Keywords: Rubin, Randy; Warner, Julian; Morries, Mark; Manfredi, David; Whited, Jim; Chavez, Pat; Neal, Jeff; Christmas Music; Christmas Performance; Live Performance; Music Ensemble; Raton, New Mexico